Evidence-based recommendations for the management of undifferentiated peripheral inflammatory arthritis (UPIA). The German perspective on the international 3e initiative - Tarner, I. H.; Albrecht, K.; Fleck, M.; Gromnica-Ihle, E.; Keysser, G.; Koehler, L.; Koetter, I.; Krueger, K.; Kuipers, J.; Nuesslein, H.; Rubbert-Roth, A.; Wollenhaupt, J.; et al. (Zeitschrift für Rheumatologie, 2014)
Peripheral arthritis is the most common presenting complaint in clinical rheumatology. Unequivocal identification of the underlying entity can be difficult, particularly at an early stage. Such cases are commonly referred to as undifferentiated peripheral inflammatory arthritis (UPIA). Since evidence-based recommendations for the clinical management of UPIA are lacking, this international 3e initiative convened 697 rheumatologists from 17 countries to develop appropriate recommendations.Based on a systematic literature research in Medline, EMBASE, Cochrane Library, and the ACR/EULAR abstracts of 2007/2008, 10 multinational recommendations were developed by 3 rounds of a Delphi process. In Germany, a national group of experts worked on 3 additional recommendations using the same method. The recommendations were discussed among the members of the 3e initiative and the degree of consensus was analyzed as well as the potential impact of the recommendations on clinical practice.A total of 39,756 references were identified, of which 250 were systematically reviewed for the development of 10 multinational recommendations concerning differential diagnosis, diagnostic and prognostic value of clinical assessments, laboratory tests and imaging techniques, and monitoring of UPIA. In addition, 3 national recommendations on the diagnostic and prognostic value of a response to anti-inflammatory therapy on the analysis of synovial fluid and on enthesitis were developed by the German experts based on 35 out of 5542 references.The article translates the 2011 published original paper of the international 3e initiative (Machado et al., Ann Rheum Dis 70:15-24, 2011) and reports the methods and results of the national vote and the additional 3 national recommendations.
EVALuna2:12975